Conferences 4 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
ConferencesEmpowering farmers through animal traction in 21st century20 - 24 September 1999, South AfricaThis conference will be held in Mpumalanga, South Africa.Contact:Bruce Joubert, ATNESA/SANAT Workshop secretariat.Fax: +27 4065 31730Email:...